Boosting Electrical Performance of High-κ Nanomultilayer Dielectrics and Electronic Devices by Combining Solution Combustion Synthesis and UV Irradiation - Carlos, Emanuel (2019)
Grant SFRH/BPD/99136/2013 Grant SFRH/BD/122286/2016 Grant SFRH/BD/116047/2016 IDS-FunMat-INNO project FPA2016/EIT/EIT RawMaterials Grant Agreement 15015.